VO#055 Quotation for cable trench and shaft well work rev.00 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of quotation for cable trench and shaft well work of BRACU new campus project.